Still Life with Mother and Knife : Poems - Rathburn, Chelsea, 1975- (Book collections on Project MUSE., 2019)
In Still Life With Mother and Knife, Chelsea Rathburn tells us that we inhabit our own fairy tales, and we have to learn to walk alone in the woods-- the briary forests of adolescences, the dark drifts of motherhood, and then the lonely sands of old age."-- From back cover.